Investigation machining-surface integrity-wear resistance relationships of 316LVM stainless steel material machined under various cutting parameters - ŞİRİN, TOLGA; KAYNAK, YUSUF (PAMUKKALE UNIV, 2021)
Austenitic 316LVM stainless are widely used in biomedical industry in particular medical surgical applications, and implant materials. In biomedical applications, especially implants used in the body are exposed to tribological conditions that cause wear behavior. Wear behavior of Implants fabricated by using these materials related to the surface conditions. One of the important processes influencing the surface properties used in fabricating process of implant is machining operation. For this reason, the effect of machining parameters and condition on the surface properties of this material and eventually altering the wear response is the focus of this current research. In this paper, dry milling operations of Austenitic 316LVM under various parameters were presented. The surface roughness, microhardness, microstructure are the examined surface integrity characteristics in this study. The effect of generated characteristics resulting from machining on wear resistance is measured using pin-on-disc test It was revealed that cutting speed and feed has notable effect on surface roughness and strain hardening of the specimen. Increased strain hardening generally results in decreased wear resistance while increased surface roughness results in increased wear resistance.
Keywords: 316LVM stainless steel; Machining; Surface integrity; Wear behavior; CORROSION